2015
DOI: 10.1007/8904_2015_478
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Expansion of Congenital Disorder of Glycosylation Due to SRD5A3 Null Mutation

Abstract: We present a boy, admitted at 4 months, with facial dysmorphism, hypertrichosis, loose skin, bilateral inguinal hernia, severe hypotonia, psychomotor disability, seizures with hypsarrhythmia (West syndrome), hepatosplenomegaly, increased serum transaminases, iris coloboma, glaucoma, corneal clouding and bilateral dilated lateral ventricles, and extra-axial post-cerebellar space. Serum transferrin isoelectrofocusing (IEF) showed a type 1 pattern. Whole-exome genotyping showed a previously reported homozygous no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
(22 reference statements)
1
8
1
Order By: Relevance
“…In addition, our patient had facial coarseness and inverted nipples, not described in previously reported patients. He did not have short stature and had normal serum IGFBP3 in contrast to previously described cases 9 . Others have shown that although both inter- and intra-familial variability occurs, but no specific genotype, phenotype correlation has been observed in these patients 5 7 .…”
contrasting
confidence: 60%
See 2 more Smart Citations
“…In addition, our patient had facial coarseness and inverted nipples, not described in previously reported patients. He did not have short stature and had normal serum IGFBP3 in contrast to previously described cases 9 . Others have shown that although both inter- and intra-familial variability occurs, but no specific genotype, phenotype correlation has been observed in these patients 5 7 .…”
contrasting
confidence: 60%
“…SRD5A3 -CDG (CDG1Q; MIM 612379) has been a recently described steroid 5a-reductase type 3 defects with broad clinical phenotype. Till date, only 20 patients from 14 families have been described worldwide 3 4 5 6 7 8 9 . We describe here an Indian case of SRD5A3 -CDG identified by exome sequencing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study had detected duplication at 4q11–q13.1 in patients with idiopathic short stature, and TMEM165 and POLR2B in this region were suspected as candidate genes for growth retardation ( 36 , 37 ). The duplication also included the SRD5A3 gene, the cause of Kahriz syndrome, and the null mutation of SRD5A3 having been reported to be associated with the epileptic phenotype, WS ( 38 ). In the duplicated regions, we also considered the REST gene as another candidate disease-causing gene because of its potential to control fundamental transcription patterns that drive circuit excitability, seizures, and epilepsy ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…The broad clinical spectrum observed in patients with SRD5A3 mutations shows many similarities with other ER-related glycosylation defects including psychomotor retardation and cerebellar ataxia. These symptoms result from likely null SRD5A3 alleles ( Kara et al, 2014 ; Tuysuz et al, 2016 ) ( Wheeler et al, 2016 ) ( Cantagrel et al, 2010 ) ( Gründahl et al, 2012 ) and reflect impaired protein N-glycosylation, as previously described in yeast and mouse embryos mutated for the corresponding SRD5A3 ortholog ( Cantagrel et al, 2010 ). Here, we sought to gain mechanistic and functional insight into protein N-glycosylation during neural development, so we used conditional disruption of the Srd5a3 gene in the mouse cerebellum, a tissue often affected in CDG.…”
Section: Introductionmentioning
confidence: 82%